Understanding the Phyllanthus and Terminalia chebula Species Population Change, Dependency and Sustainability: A Study in Malai Mahadeshwara Hills Wildlife Sanctuary, Southern India - Harisha, R.P.; Siddappa, Setty R.; Ravikanth, G. (International Journal of Environment, 2023)
Non-Timber Forest Products (NTFPs) are vital sources of livelihood for forest-dependent communities across the globe. This study examined the NTFPs species (Phyllanthus emblica, P. indofischeri, and Terminalia chebula) population change determined by the dependency, disturbances, and accessibility in the dry tropical forest of Malai Mahadeshwara (MM) Hills wildlife sanctuary. The long-term monitoring population data were analyzed across three time periods; 2000-01, 2010-11, and 2020-21. The participatory research methods were used to assess the dependency and accessibility which influence the population structure. The multi-factor linkage approach was used to identify the significant drivers of population decline. The results indicated that grazing, fire, hemi-parasite infection, and Lantana invasion influenced the tree population structure and regeneration of study species. This study has also indicated variations and changes in the interrelationship among factors that have a significant role in shaping NTFPs species population structure. Multiple factor analysis determined that grazing, fire, and lantana have significant impacts on population structures, regeneration, and fruit production of NTFPs species. The study recommended that forest managers should consider a site-specific adaptive approach and multiple factors models and inclusive management tools provisioned in recent policies like the Biological Diversity Act -2002 and Forest Rights Act-2006 would hold great potential for developing sustainable use and co-management practices.